Live-In Relationships: Challenges & Acceptance - Mali, Sparsh; Dutta, Preyasi (International Journal of Law, Human Rights and Constitutional Studies, 2020)
Human-being is the most advanced and eminently skilled species on this planet, which has gone through most advance dynamic evolution and adoption which led human to change from simple structure of relation to most complex relationship i.e., Live-In relationship. And these changes divulge new patterns in sharing their love as romance & sexual relationship without coming in legally binding relationship in India. But these types of relationship are highly challenged in India as it is against the Indian culture & values. Being India as a democratic country and giving liberty to every individual, enhance the power of an individual to live according to his/her will and by making Right to Privacy as Fundamental Right of the individual gives partially right to every individual to live with anybody and in any form. These principles help people to continue into Live-In relationship and should be unquestionable & unchallengeable by any form of group or society on grounds of historic culture/customs. As on today, there isn’t any special act or even any clause on Live-In relationship in India which tells about the legality of this relationship as being practised in some countries like USA, UK, and Scotland etc. This Paper will collate the Live-In relationship status in India with other Countries and will try to analyse the current situation & suggest us measures by which we can solve this problem in our country. This will also suggest us why Live-In relationship is a need of an hour. How to cite this article:  Mali S, Dutta P. Live-In Relationships: Challenges & Acceptance. Int Jour Law Hum Rights Const Stud 2021; 2(1): 1-5.